Analysis of Quiet Time Vertical Ionospheric Delay Gradients Around Suvarnabhumi Airport, Thailand. Issue 9 (14th September 2018) - Budtho, J.; Supnithi, P.; Saito, S.
Abstract: Global Navigation Satellite System (GNSS) is vital to aircraft navigation at many phases of flight. To extend its use to the approach and landing phases, ground‐based augmentation system is an important on‐the‐ground technology to reduce the positioning errors. However, nonuniform spatial ionospheric delays need to be assessed during ground‐based augmentation system planning at each airport, particularly, in equatorial and low‐latitude regions. In this work, we analyze the statistics of ionospheric delay gradients around Suvarnabhumi airport, Thailand. The ionospheric delay gradients are estimated using single‐frequency code and carrier phase observation through the Kalman filter. To increase the success of the ratio test, the satellite elimination technique is then proposed. Based on the analysis between 2013 and 2016, we find that the background ionospheric delay gradients during equinox are higher than solstice, especially during September equinox 2013 when the gradients are about 9 mm/km. Moreover, the ionospheric delay gradients are more variable during daytime than nighttime. Key Points: The paper focuses on the statistics of quiet time vertical ionospheric delay gradients around Suvarnabhumi Airport, Thailand The single‐frequency‐based method is used to estimate the ionospheric delay gradient under daytime, nighttime, and seasonal conditions The results show that the background ionospheric delay gradients during equinox are higher than during solstice and fluctuate during daytime more than nighttime